2022
DOI: 10.1007/s00406-022-01496-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered psychobiological reactivity but no impairment of emotion recognition following stress in adolescents with non-suicidal self-injury

Abstract: Impairments in both stress regulation and emotion recognition have been associated with borderline personality disorder (BPD) and non-suicidal self-injury (NSSI). Although it has been proposed that emotion recognition deficits particularly emerge during stress, this hypothesis has not been fully investigated. Adolescents with and without NSSI performed emotion recognition tasks before and after the employment of the Trier Social Stress Test (TSST). The psychobiological stress response was captured with psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 73 publications
4
16
0
Order By: Relevance
“…Given that BPD often presents with NSSI (e.g., Nock et al, 2006) and is associated with greater affect instability (for reviews, see Houben et al, 2015;Schmahl et al, 2014), researchers have suggested that altered subjective and physiological responding in NSSI may reflect underlying dimensional BPD psychopathology (Hooley & Franklin, 2018;Kaess et al, 2021). In line with this proposal, Koenig et al, (2022) recently demonstrated that negative affect and heart rate reactivity to stress differed not only between adolescents with and without NSSI, but also as a function of dimensional BPD severity. Thus, these mixed findings may indicate that amplified emotional responding is comorbid with, rather than characteristic of, NSSI.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Given that BPD often presents with NSSI (e.g., Nock et al, 2006) and is associated with greater affect instability (for reviews, see Houben et al, 2015;Schmahl et al, 2014), researchers have suggested that altered subjective and physiological responding in NSSI may reflect underlying dimensional BPD psychopathology (Hooley & Franklin, 2018;Kaess et al, 2021). In line with this proposal, Koenig et al, (2022) recently demonstrated that negative affect and heart rate reactivity to stress differed not only between adolescents with and without NSSI, but also as a function of dimensional BPD severity. Thus, these mixed findings may indicate that amplified emotional responding is comorbid with, rather than characteristic of, NSSI.…”
Section: Discussionmentioning
confidence: 98%
“…We offer three possible avenues for investigation. First, research to date has focused on emotional responding to strong negative challenges (e.g., acute stress, Kaess et al, 2012;Koenig et al, 2022;Tatnell et al, 2018), raising concerns about potential ceiling effects. More subtle interpersonal challenges may better capture the nature of emotion dysregulation in NSSI (although see, Robinson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that individuals engaged in NSSI showed suppression of vagus nerve-mediated HRV while at rest 65 . Such finding suggested that the activity of the parasympathetic nervous system in individuals engaged in NSSI decreases during the resting state, suggesting that the sympathetic nervous system activity may be the main component of NSSI neural activity 66 . Therefore, the ED in NSSI may be related to the low level of parasympathetic nervous system activity and the high level of sympathetic nervous system activity, which requires further research to prove this hypothesis.…”
Section: Nonsuicidal Self-injury and Emotional Dysregulationmentioning
confidence: 98%